PEMBENTUKAN KARAKTER KEDISPLINAN SANTRI DI PONDOK PESANTREN MELALUI METODE PEMBIASAAN - Muhammad Fathin Abdul Ghoffar; Joko Subando (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
In the ever-evolving world of education, educators are required to find effective methods for shaping students' character. One relevant and proven effective method is the habituation method. This study aims to describe the role of the habituation method in shaping student discipline in Islamic boarding schools (pesantren) as character education institutions. This study used a qualitative approach with a literature review, through a review of various literature discussing character, discipline, and habituation methods. The results show that the habituation method, when implemented consistently and repeatedly, is able to instill positive values such as discipline in students. This process is supported by the role of the kyai (Islamic religious leader) as a role model and supervisor who is directly involved in fostering student behavior. In Islamic boarding schools, education takes place holistically, encompassing spiritual, social, and moral aspects, making habituation a strategic approach in shaping student personality. The conclusion of this study confirms that the habituation method needs to be strengthened within the Islamic boarding school curriculum system as an effective and applicable model of character education.